A efetividade da recuperação da atividade econômica dos clubes de futebol no Brasil - Pedro, Paulo Roberto Bastos (2024)
This paper aims to examine sports activities, with a particular focus on football, and demonstrate the extent to which sports generally have a positive impact on people’s daily lives. This influence is not only due to the recreational opportunities they offer but also because sports play a significant role in the entertainment industry and in professional career development. The study further seeks to illustrate how clubs, especially those whose primary focus is football, have transitioned from being social clubs to predominantly highperformance sports institutions with less emphasis on social interaction. The research underscores the pivotal role these clubs have played in social development, particularly in the city of São Paulo. The analysis delves into the crisis that many clubs are currently experiencing, largely due to changes in revenue sources, and explores the main sources of revenue in contemporary times, showing how these clubs have redefined their operational models since their inception. The study also discusses the significance and autonomy granted to sports organizations by the Federal Constitution, as well as recent legislative measures aimed at helping clubs overcome the economic and financial crises faced by many football clubs. This examination is based on the assumption that restructuring mechanisms (both judicial and extrajudicial), as outlined in Law 11.101/2005, could be applied to sports clubs even before legislative approval was granted through Law 14.193/2021. The recent legislative changes are essential for sustaining the activities of these clubs, facilitating their recovery from economic and financial distress, which, in turn, preserves jobs and social activities. Most importantly, these changes help maintain the enduring passion for football among the community of fans and supporters